Disparities in cancer care and outcomes by insurance membership type in Indonesia: a retrospective cross-sectional analysis of national health insurance claims, 2017–2022 - Dian Kusuma; Ede Surya Darmawan; Syarif Rahman Hasibuan; Vetty Yulianty Permanasari (BMJ Open, 2025)
Objectives To examine disparities in health services and outcomes for cancer among different membership types within the national health insurance in Indonesia.Design and setting This study employed a retrospective cross-sectional analysis of health insurance claim data. The setting was inpatient claims from public and private hospitals across Indonesia during 2017–2022. We assessed the associations between membership types in the National Health Insurance system (Badan Penyelenggara Jaminan Sosial Kesehatan, BPJS) and six dependent variables: receipt of biopsy, transfusion of packed red blood cells or platelets, length of hospital stay, claim costs (natural log-transformed), disease severity (moderate or severe) and in-hospital mortality.Participants We analysed 34 904 inpatient claim records for patients with cancer aged 16 years and older enrolled in BPJS. Membership types included: the poorest members subsidised by the national budget (Penerima Bantuan Iuran Anggaran Pendapatan dan Belanja Negara, PBI APBN); near-poor members subsidised by local governments (Penerima Bantuan Iuran Anggaran Pendapatan dan Belanja Daerah—PBI APBD); informal non-workers (Bukan Pekerja, BP); informal workers (Pekerja Bukan Penerima Upah, PBPU) and formal workers (Pekerja Penerima Upah, PPU).Results Significant disparities were observed across BPJS membership types. Compared with the poorest group (PBI APBN), informal non-workers (BP) and informal workers (PBPU) had higher odds of receiving transfusions (adjusted OR (AOR): 1.43 and 1.26, respectively), while formal workers (PPU) had shorter hospital stays (−0.27 days) and higher claim costs. Interestingly, PBI APBN members had greater odds of receiving biopsies than PBI APBD (AOR: 0.62) and PPU (AOR: 0.77) members. In terms of health outcomes, PBI APBN members experienced higher odds of severe cases and mortality, whereas PPU members had significantly lower odds of severity (AOR: 0.78) and death (AOR: 0.67).Conclusion Substantial socioeconomic disparities persist in cancer diagnostics, treatment and outcomes among BPJS members. Poorer groups face greater barriers to care and worse outcomes. Policies should prioritise equitable cancer care access for low-income and subsidised members of Indonesia’s national health insurance.